10 year survival after breast-conserving surgery plus radiotherapy compared with mastectomy in early breast cancer in the Netherlands: a population-based study - van Maaren, Marissa C; de Munck, Linda; de Bock, Geertruida H; Jobsen, Jan J; van Dalen, Thijs; Linn, Sabine C; Poortmans, Philip; Strobbe, Luc J A; Siesling, Sabine (The lancet oncology, 2016)
Investigators of registry-based studies report improved survival for breast-conserving surgery plus radiotherapy compared with mastectomy in early breast cancer. As these studies did not present long-term overall and breast cancer-specific survival, the effect of breast-conserving surgery plus radiotherapy might be overestimated. In this study, we aimed to evaluate 10 year overall and breast cancer-specific survival after breast-conserving surgery plus radiotherapy compared with mastectomy in Dutch women with early breast cancer. In this population-based study, we selected all women from the Netherlands Cancer Registry diagnosed with primary, invasive, stage T1–2, N0–1, M0 breast cancer between Jan 1, 2000, and Dec 31, 2004, given either breast-conserving surgery plus radiotherapy or mastectomy, irrespective of axillary staging or dissection or use of adjuvant systemic therapy. Primary outcomes were 10 year overall survival in the entire cohort and breast cancer-specific survival in a representative subcohort of patients diagnosed in 2003 with characteristics similar to the entire cohort. We estimated breast cancer-specific survival by calculating distant metastasis-free and relative survival for every tumour and nodal category. We did multivariable Cox proportional hazard analysis to estimate hazard ratios (HRs) for overall and distant metastasis-free survival. We estimated relative survival by calculating excess mortality ratios using life tables of the general population. We did multiple imputation to account for missing data. Of the 37 207 patients included in this study, 21 734 (58%) received breast-conserving surgery plus radiotherapy and 15 473 (42%) received mastectomy. The 2003 representative subcohort consisted of 7552 (20%) patients, of whom 4647 (62%) received breast-conserving surgery plus radiotherapy and 2905 (38%) received mastectomy. For both unadjusted and adjusted analysis accounting for various confounding factors, breast-conserving surgery plus radiotherapy was significantly associated with improved 10 year overall survival in the whole cohort overall compared with mastectomy (HR 0·51 [95% CI 0·49–0·53]; p<0·0001; adjusted HR 0·81 [0·78–0·85]; p<0·0001), and this improvement remained significant for all subgroups of different T and N stages of breast cancer. After adjustment for confounding variables, breast-conserving surgery plus radiotherapy did not significantly improve 10 year distant metastasis-free survival in the 2003 cohort overall compared with mastectomy (adjusted HR 0·88 [0·77–1·01]; p=0·07), but did in the T1N0 subgroup (adjusted 0·74 [0·58–0·94]; p=0·014). Breast-conserving surgery plus radiotherapy did significantly improve 10 year relative survival in the 2003 cohort overall (adjusted 0·76 [0·64–0·91]; p=0·003) and in the T1N0 subgroup (adjusted 0·60 [0·42–0·85]; p=0·004) compared with mastectomy. Adjusting for confounding variables, breast-conserving surgery plus radiotherapy showed improved 10 year overall and relative survival compared with mastectomy in early breast cancer, but 10 year distant metastasis-free survival was improved with breast-conserving surgery plus radiotherapy compared with mastectomy in the T1N0 subgroup only, indicating a possible role of confounding by severity. These results suggest that breast-conserving surgery plus radiotherapy is at least equivalent to mastectomy with respect to overall survival and may influence treatment decision making for patients with early breast cancer. None.